Lobelia trigona Roxb-based nanomedicine with enhanced biological applications: in vitro and in vivo approach - Samdavid Thanapaul, Rex Jeya Rajkumar; Manikandan, Sreeraj K; Govindaraj, Tamil Selvan; Selvakumar, Paulraj Mosae; Enoch, Israel V.M.V; Muthukumar Nadar, Meenakshi Subbaraman Adyanpuram (IET nanobiotechnology, 2020)
This is the first study to report the green synthesis of Lobelia trigona Roxb-mediated silver nanoparticles (LTAgNPs). The optical and structural properties of the synthesised LTAgNPs were analysed using ultraviolet–visible spectroscopy, scanning electron microscopy, Fourier transform infrared, dynamic light scattering and energy dispersive X-ray. LTAgNps were evaluated for their anti-bacterial and anti-fungal properties against 18 pathogens and exhibited significant inhibition against all the strains tested. LTAgNPs had potential scavenging effects on the DPPH, •OH, O2•− free radical scavenging assays and reducing power assay. LTAgNps possess strong anti-cancer activity against five human cancer cell lines (A549, MCF-7, MDA-MB-231, HeLa and KB) in a dose-dependent manner. The antiproliferative, anti-inflammatory and genotoxicity effects of LTAgNPs were further confirmed by the lactate dehydrogenase release assay, nitric oxide inhibitory assay and comet assay. Furthermore, the incision, excision and burn wound-healing activity of formulated LTAgNPs ointment was assessed in rats. All the wounds had significant healing in groups treated with LTAgNPs ointment compared to the groups treated with the commonly prescribed ointment (SilverexTM). This study shows and suggests that the previously unreported LTAgNPs could be used as a nanomedicine with significant biological applications.